A Recent Update on the Epigenetic Repertoire and Chromatin Modifying Therapy in Diabetes Mellitus: A Comprehensive Review - Wang, Xin; Zhao, Di; Beeraka, Narasimha M.; Tatineni, Spandana; Sri, Chiriki Devi; Nishanth, Veera Venkata; Uthiah, Chinnappa Apatira; Leihang, Zonunsiami; Sugur, Kavya; Liu, Junqi; Nikolenko, Vladimir Nikolaevich; Fan, Ruitai (Current Medicinal Chemistry, 2023)
Several epigenome studies reported the ability of genes to modulate the lipogenic and glucogenic pathways during insulin signaling as well as the other pathways involved in cardiometabolic diseases. Epigenetic plasticity and oxidative stress are interrelated in the pathophysiology of insulin resistance (IR) and cardiometabolic disease conditions. This review aims to ascertain the previous research evidence pertaining to the role of the epigenome and the variations of histone and non-histone proteins during cardiometabolic disease conditions and insulin signaling to develop effective disease-based epigenetic biomarkers and epigenetics-based chromatic therapy. Several public databases, including PubMed, National Library of Medicine, Medline, and google scholar, were searched for the peer-reviewed and published reports. This study delineates the consistent body of evidence regarding the epigenetic alterations of DNA/histone complexes pertinent to oxidative stress, insulin signaling, metabolic cardiomyopathy, and endothelial dysfunction in patients with cardiometabolic diseases. It has been described that both DNA methylation and post-translational histone alterations across visceral and subcutaneous adipose tissue could facilitate gene transcription to modulate inflammation, lipogenesis, and adipogenesis as the complex network of chromatin-modifying enzymatic proteins involved in the defensive insulin signaling across vasculature in patients with cardiometabolic diseases. Resveratrol, vorinostat, trichostatin, and apabetalone are reported to have significant implications as epigenetic modulators. Based on the epigenetic alterations, a wide range of protein/gene markers, such as interleukin-4 (IL-4) and interferon-γ (IFNγ) genes, may be considered as biomarkers in these patients due to their ability to the polarization of immune cells involved in tissue inflammation and atherosclerosis. Hence, it is crucial to unravel the cell-specific epigenetic information to develop individual risk assessment strategies for chromatin-modifying therapies in patients with cardiometabolic diseases.
Keywords: cardiometabolic diseases